On the ionic conductivity of some zirconia-derived high-entropy oxides. Issue 8 (July 2021) - Bonnet, E.; Grenier, J.C.; Bassat, J.M.; Jacob, A.; Delatouche, B.; Bourdais, S.
Abstract: The reported High Entropy Oxides (HEOs) up to now exhibit lower ionic conductivity values than those of classical SOFC electrolytes. Multi-cations oxides, stabilized with the fluorite-type structure are investigated here in order to examine whether the high entropy is relevant to enhance the anionic conductivity of such HEOs, or not. The two synthesis routes that are used do not show significant impact on material properties. Based on configurational entropy (≥ 1.5 kB /f.u. for HEOs) and ionic radius difference calculations, new compositions are designed and prepared: i) the (Hf1/3 Ce1/3 Zr1/3 )1-x (Gd1/2 Y1/2 )x O2-x/2 series in which the x ratio is increased so as to promote a high vacancy concentration, ii) the (Hfx Cey Zr1-x-y )0.85 Yb0.15 O1.93 series based on the critical radius concept. The ionic conductivity of these HEOs is slightly improved compared to previously reported data but does not exceed 4 × 10 −4 S.cm −1 at 600 °C. Possible causes of such a low ionic conductivity value are discussed.